Antara Degradasi dan Ekspektasi: Menuju Pesta Demokrasi Pemilukada Tahun 2024 di Indonesia - Yanto, Adri; Bariki, Yusril (Prodi Tata Negara (Siyasah) IAIN Langsa, 2024)
Pemilukada is a representative of the principle of decentralization which is proclaimed in the form of regional autonomy as stipulated in Law Number 32 of 2004 concerning Regional Government. The rise of money politics and non-neutral bureaucracy are a series of real problems. So what is the concept of post-conflict local elections in Indonesia? Is it ideal or has it degraded democratic values? Is it just a mere expectation? In this research, the approach used is normative juridical, which is based on a literature review regarding the simultaneous regional elections in 2024. The data collection technique and arguments developed in this paper use a research library, namely by collecting various scientific reference sources from primary sources and secondary sources through related writings. The results of the research show that the existence of the Regional Head Election has a degradation side in terms of holding a neutral bureaucracy and intelligent voters. In fact, in terms of expectations, several ideal elements must be fulfilled in holding the Regional Election, both in terms of precise and clear regulations, competent political parties, intelligent voters, as well as independent organizers, and a neutral bureaucracy. So that the constitutional mandate will be achieved and also produce trustworthy leaders, who have integrity and are democratic.